Two isomeric compounds from Streptomyces species and their antimicrobial activity - Sathi, Zakia Sultana; Habib, Md. Anwar; Anisuzzaman, Abu Syed Md.; Islam, Md. Anwarul (Bangladesh Journal of Pharmacology, 2010)
<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-fareast-language: ja; mso-bidi-language: ar-SA;" lang="en-US">The chloroform extract of the culture filtrate of an isolated <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-US; mso-ansi-language: en-US; mso-fareast-language: ja; mso-bidi-language: ar-SA;" lang="en-US">Streptomyces<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-fareast-language: ja; mso-bidi-language: ar-SA;" lang="en-US"> species upon chromatographic analysis had lead to the isolation of two isomeric compounds (I and II). The structure of the compounds was considered to be Stretomysone A (I) and Streptomysone B (II) by its spectral data. Both the compounds showed significant antimicrobial activity against tested pathogenic bacteria and fungus. The compounds seem to be first report of isomeric compound from <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-US; mso-ansi-language: en-US; mso-fareast-language: ja; mso-bidi-language: ar-SA;" lang="en-US">Streptomyces<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-fareast-language: ja; mso-bidi-language: ar-SA;" lang="en-US"> species having antimicrobial activity.